Politik Hukum Kewenangan Mahkamah Konstitusi Terhadap Pengujian Peraturan Pemerintah Pengganti Undang-Undang - Yanuar, Muh. Afdal (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
This paper aims to describe the legal considerations that underlie the authority of the Constitutional Court on judicial review of government regulations in substitute of law, and legal policy of the authority of the Constitutional Court on judicial review of government regulations in lieu of law.This is based on a situation where the judicial review authority by the Constitutional Court as regulated in the Constitution only contains the review of the law to the Constitution. However, in its dynamics, through the Decision of the Constitutional Court Number 138/PUU-VII/2009, it has expanded the meaning of the ‘law’, to include the government regulations in substitute of law, which some experts view that the government regulations in lieu of law is a ‘law’ in a material sense (wet in materiele zijn). This paper uses normative research. In this paper, it is stated that the decision of the constitutional court to make government regulations in lieu of law as an object that can be reviewed in the Constitutional Court, is an embodiment of the philosophy of judicial activism, which reflects the responsiveness of the Constitutional Court to the legal vacuum of reviewing government regulations in lieu of law, if it is judged to be formally or materially defects by parties who have legal standing over that. The results of the research presented in this paper are, first, the legal considerations so that the Constitutional Court has the authority to review the government regulations in lieu of laws as stated in the Constitutional Court's Decision Number 138/PUU-VII/2009, which abstractly refers to the nature of the content of the government regulations in lieu of laws which is the same as the law. Second, the authority of the Constitutional Court in judicial review, which is also authorized to review the constitutionality of government regulations in lieu of laws, since the Constitutional Court Decision Number 138/PUU-VII/2009, is a form of transformation of authority that is realized through the legal politics on the authority of the Constitutional Court without going through legislative process in parliament